Carbon capture and storage (CCS): the way forward. Issue 5 (12th March 2018) - Bui, Mai; Adjiman, Claire S.; Bardow, André; Anthony, Edward J.; Boston, Andy; Brown, Solomon; Fennell, Paul S.; Fuss, Sabine; Galindo, Amparo; Hackett, Leigh A.; Hallett, Jason P.; Herzog, Howard J.; et al.
Abstract : Carbon capture and storage (CCS) is vital to climate change mitigation, and has application across the economy, in addition to facilitating atmospheric carbon dioxide removal resulting in emissions offsets and net negative emissions. This contribution reviews the state-of-the-art and identifies key challenges which must be overcome in order to pave the way for its large-scale deployment. Abstract : Carbon capture and storage (CCS) is broadly recognised as having the potential to play a key role in meeting climate change targets, delivering low carbon heat and power, decarbonising industry and, more recently, its ability to facilitate the net removal of CO2 from the atmosphere. However, despite this broad consensus and its technical maturity, CCS has not yet been deployed on a scale commensurate with the ambitions articulated a decade ago. Thus, in this paper we review the current state-of-the-art of CO2 capture, transport, utilisation and storage from a multi-scale perspective, moving from the global to molecular scales. In light of the COP21 commitments to limit warming to less than 2 °C, we extend the remit of this study to include the key negative emissions technologies (NETs) of bioenergy with CCS (BECCS), and direct air capture (DAC). Cognisant of the non-technical barriers to deploying CCS, we reflect on recent experience from the UK's CCS commercialisation programme and consider the commercial and political barriers to the large-scale deployment of CCS. In all areas, we focus on identifying and clearly articulating the key research challenges that could usefully be addressed in the coming decade.